2014
DOI: 10.1074/jbc.m113.523753
|View full text |Cite
|
Sign up to set email alerts
|

Functional Evaluation of Activation-dependent Alterations in the Sialoglycan Composition of T Cells

Abstract: Background: Sialic acids play key roles in molecular recognition. Results: T-cell activation alters the principal sialic acid species profile, regulating expression of siglec ligands, T-cell activation per se, and T cell-B cell interactions. Conclusion: This activation-dependent change in the sialoglycan profile modulates immune responses. Significance: Pronounced changes in the sialoglycan profile not only serve as cellular markers but also reflect cellular functionality.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
19
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(22 citation statements)
references
References 59 publications
(69 reference statements)
2
19
0
Order By: Relevance
“…Interestingly, it has been reported that both resting T-and B-cells preferentially carry Neu5Gc in ␣-2,6-linkage. Cell activation, however, results in marked changes in the glycosylation pattern, including a shift to Neu5Ac in ␣-2,3-linkage (36,66). As a result, expression of Siglec-1 and Siglec-E ligands is enhanced on these lymphocytes.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, it has been reported that both resting T-and B-cells preferentially carry Neu5Gc in ␣-2,6-linkage. Cell activation, however, results in marked changes in the glycosylation pattern, including a shift to Neu5Ac in ␣-2,3-linkage (36,66). As a result, expression of Siglec-1 and Siglec-E ligands is enhanced on these lymphocytes.…”
Section: Discussionmentioning
confidence: 99%
“…Another possibility where unmasking of CD22 on GC B-cells could make an impact is in B-T cell interactions (32). Indeed, several studies have suggested that CD22 can modulate B-T cell interactions (12,(32)(33)(34)(35). Decreased cis ligands on GC B-cells could also be a means of modulating the interactions between CD22 and the BCR to regulate B-cell signaling or endocytosis.…”
Section: Discussionmentioning
confidence: 99%
“…As coordinated movement of GC B-cells between the light zone and dark zone of the GC is critical in the selection process (14), CD22 could participate in this migration. Another possibility where unmasking of CD22 on GC B-cells could make an impact is in B-T cell interactions (32). Indeed, several studies have suggested that CD22 can modulate B-T cell interactions (12,(32)(33)(34)(35).…”
Section: Discussionmentioning
confidence: 99%
“…Over the last years, several papers have demonstrated the importance of differential sialylation for CD8 + T cells with respect to their maturation ( Moody et al, 2001 ; Naito-Matsui et al, 2014 ), activation ( Pappu and Shrikant, 2004 ), and cytotoxic responses ( Sadighi Akha et al, 2006 ). However, few studies provided insights into the impact of surface sialylation of CD8 + T cells on infectious diseases.…”
Section: Discussionmentioning
confidence: 99%